Genetic Dissection of qPCG1 for a Quantitative Trait Locus for Percentage of Chalky Grain in Rice (Oryza sativa L.) - Zhu, Aike; Zhang, Yingxin; Zhang, Zhenhua; Wang, Beifang; Xue, Pao; Cao, Yongrun; Chen, Yuyu; Li, Zihe; Liu, Qunen; Cheng, Shihua; Cao, Liyong (Frontiers in Plant Science, 2018)
Rice is a pivotal cereal crop that provides the staple food for more than half of the world’s population. Along with improvements in the standard of living, people not only pay attention to the grain yield but also to the grain quality. Chalkiness is one of the most important index of grain quality. In this study, qPGWC-1, a QTL controlling percentage of grains with chalkiness, was mapped in an interval with a physical distance about 139Kb on chromosome 1 by residual heterozygous line method. qPGWC-1 is incomplete dominant and the additive effect plays a major role and the contribution rate is from 6.8 to 21.9%. The effect of allele from Zhonghui9308 is decreasing the percentage of grains with chalkiness. SEM results indicate that there are great differences in the shape, structure and arrangement of starch granule between the chalky part and transparent part. qPGWC-1 has little influence on main agronomic traits and it might be useful in rice breeding for it does not bring negative effect on grain yield while reducing the chalkiness.